Audit Quality, Firm Value And Earnings Management - Setyawan, Deva; Ghozali, Imam (E-Jurnal Akuntansi; Vol 35 No 7 (2025), 2025)
The research aims to find out empirically the mediated relationship of audit quality mediation to the company's value through profit management. Audit quality is measured based on the size of the audit firm, industry specialization, and audit costs. This study is motivated by the rampant profit management practices in the mining sector that have the potential to harm investors, even though they have been audited by professional firms. Different from previous research, this study highlights the specific role of audit quality elements as a controlling mechanism of profit management mediation on company value. The study was conducted on 59 companies focused on the mining sector listed on the IDX for the period 2021 – 2023. The data analysis technique uses CEM estimation with direct regression and mediation models. The findings of this research are that there is a negative influence on industry specialization and costs on profit management. There is no evidence of the influence of audit firm size on profit management. There is a positive relationship between audit firm size and industry specialization on company value, but audit costs have not been shown to have a relationship with company value. The relationship of profit management has a negative influence on profit management. Mediation tests have proven that profit management mediates the influence of industry specialization and audit costs on a company's value, but it does not mediate the size of the audit firm. This research contributes to enriching the literature on audit quality as a mechanism for controlling profit management and increasing company value, especially in industries that are prone to manipulation of financial statements. Keywords: Audit Quality, Firm Value, Earning Management